Meta Kecerdasan dan Kesadaran Multikultural (Kajian Pemikiran Psikologi Sufistik al-Gazali) - Abdullah Hadziq (Jurnal Ilmiah Citra Ilmu : Kajian Kebudayaan dan Keislaman, 2016)
In philosophical discourse matter of metaphysics is a perennial problem that is timeless. Among the incoming discourse in metaphysics is a matter of psychology. One of the unique variants of this study is the psychology of thinking Sufi al-Ghazali about meta intelligence and multicultural awareness. It is about the soul as a spiritual substance that has Qudrah Ilahiyyah created by the nature of al-amr, not of nature al-khalq the carnal. Ruh as a substance that psychology has a berkemapuna Latifah smart in thinking, remembering and knowing the reality of the object. This spirit in man there is a potential psychic divine (rabbaniyyah). If rabbaniyyah potential is maximized, then the person is very likely to have spiritual intelligence, which is able to bring positive implications for all behavior-based ethics divinity (morality mutakhalliq bi Allah). This conception of al-Ghzali according to the author is unique because although the soul entered the territory of the transcendental, but can also be assessed in relation to the empirical fact that is psychophysical. Therefore, when the potential divinity is continuously developed to the maximum in man, it is not impossible psychological behavior that appears likely to love kindness, compassion, and peace are based on moral and multicultural.